2007
DOI: 10.1073/pnas.0611070104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of actomyosin bond properties in intact skeletal muscle by force spectroscopy

Abstract: Force generation and motion in skeletal muscle result from interaction between actin and myosin myofilaments through the cyclical formation and rupture of the actomyosin bonds, the crossbridges, in the overlap region of the sarcomeres. Actomyosin bond properties were investigated here in single intact muscle fibers by using dynamic force spectroscopy. The force needed to forcibly detach the cross-bridge ensemble in the half-sarcomere (hs) was measured in a range of stretching velocity between 3.4 ؋ 10 3 nm⅐hs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 42 publications
4
22
0
Order By: Relevance
“…Most of our data were obtained on the tetanus rise at a tension level between 0.2 and 0.6 P 0 at which fibre damage was very much reduced. Lowering the tension was also important to reduce crossbridge strain non‐uniformity (Colombini et al 2007 b ). To determine the crossbridge rupture force, fast ramp test stretches (duration between 0.4 ms and 0.9 ms and 16–25 nm per half‐sarcomere (nm hs −1 ) amplitude, corresponding to stretching velocity of 16.9 and 59.5 fibre lengths per second ( l 0 s −1 )) were applied to one end of the activated fibre while force response was measured at the other end.…”
Section: Methodsmentioning
confidence: 99%
“…Most of our data were obtained on the tetanus rise at a tension level between 0.2 and 0.6 P 0 at which fibre damage was very much reduced. Lowering the tension was also important to reduce crossbridge strain non‐uniformity (Colombini et al 2007 b ). To determine the crossbridge rupture force, fast ramp test stretches (duration between 0.4 ms and 0.9 ms and 16–25 nm per half‐sarcomere (nm hs −1 ) amplitude, corresponding to stretching velocity of 16.9 and 59.5 fibre lengths per second ( l 0 s −1 )) were applied to one end of the activated fibre while force response was measured at the other end.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements at 5°C and 14°C were made on the same fiber in a group of 12 fibers at resting sarcomere length of about 2.1 m. Given the relative small stretches used, no change in effective overlap between myofilaments occurred during the experiments. Further details of measurements, including the correction for the first fast phase of the force response due to fiber inertia, can be found in our previous papers (1,3 Figure 1A shows the well-known potentiating effect of temperature on tetanic tension. In this fiber, tension increased by 27% as the temperature was raised from 5°C to 14°C.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that during stretch a majority of actin-bound myosin heads are attached non-stereospecifically or weakly (Ferenczi et al 2014). The rate of forced detachment of myosin heads during fast stretch of muscle fibers was shown to increase with the stretching force (Colombini et al 2007), in agreement with Bell's theory (Bell 1978).…”
Section: Introductionmentioning
confidence: 77%